Creation of a Design and Justification of Parameters of a Single-Stage Fiber Cleaner - Anvar Djuraev, Tokhir Kuliev (International Journal of Advanced Science and Technology, 2020)
The article describes the scheme and principle of operation of the fibrous material cleaner design. On the basis of solving the problem of dynamics of the fiber cleaner machine unit, the regularities of changes in the angular speeds of the saw cylinder, the engine rotor and the system load at different performance values are obtained. The parameters of the cleaner are justified. The results of research proved the effectiveness of using the cleaner.